SYSTEMATIC REVIEW: FACTORS AFFECTING NURSE'S WORK STRESS IN HOSPITAL EMERGENCY ROOM DURING THE COVID-19 PANDEMIC - Suryati, Dian Putri; Putri , Nuzulul Kusuma; Ibrahim, Normala (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: The COVID-19 pandemic has claimed millions of lives worldwide and caused a severe impact in all aspects of human life. Healthcare workers have important roles in improving the health status of the community and thus face high demand to continue to provide optimal integrated services for the community. Nurses who formed the largest group of healthcare workers have been reported to experience the high pressures and demands due to the pandemic which led to increased work stress levels. Purpose: This study aimed to identify the factors that influence work stress on nurses at the hospital's Emergency Room service during the COVID-19 pandemic. Method: This is a literature review with a population of 75 articles with the keywords used : "Work Stress", "Emergency Room" "Nurse", "Pandemic Covid-19". After going through the screening process using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method and analyzing with PICO (Population, Intervention, Comparison, Outcome), 9 reference articles were analyxed. Results: The research that has been carried out in various countries showed that the factors which drove nurses' work stress came from the internal factors of nurses and the work environment, that was the hospitals. Conclusion: The factors that drive nurses' work stress consists of individual factors and organizational factors.